Evaluasi Program Kawasan Sehat di Wilayah Layanan Kesehatan Cuma-Cuma Dompet Dhuafa Nusa Tenggara Barat dalam Upaya Pencegahan dan Penanganan Stunting: An Evaluation of Kawasan Sehat Program in Layanan Kesehatan Cuma-Cuma Dompet Dhuafa of West Nusa Tenggara for Stunting Prevention Management - Samara, Shafira Salsabila; Selawati, Selawati; Sari, Martina Tirta; Amelia, Kurnia; Wisastra, Danan Panggih; Khotibi, Zulkarnaen (Amerta Nutrition, 2024)
Background: Nutritional issues among children remain a significant health concern, with stunting being a national priority. Data of the Indonesian Nutrition Status Survey shows an increase in the prevalence of stunting in West Nusa Tenggara (NTB) from 31.4% (2021) to 32.7% (2022). Dompet Dhuafa Foundation has a Kawasan Sehat program to support the government in promoting healthy lifestyles, particularly stunting prevention. Objectives: Evaluating the Kawasan Sehat program in efforts to prevent and manage stunting in Layanan Kesehatan Cuma-Cuma area of NTB. Methods: This evaluative research used a mixed-methods approach. Data were collected through interviews, observations, and document reviews. Informants were selected using purposive sampling. Qualitative data analysis was conducted in stages of data reduction, presentation, and interpretation. Quantitative data were analyzed descriptively to assess stunting prevalence and the achievement of program indicators. Results: Kawasan Sehat program has contributed to preventing and managing stunting. The input components effectively support its implementation, with adequate human resources and budget acquired from partnerships. The program was carried out systematically, including planning involving stakeholders, execution using a combination of community empowerment and charity, and supervision. Various interventions are implemented, including support for pregnant women, breastfeeding mothers, infants, and toddlers. The success of the output was evidenced by the decrease in stunting prevalence in Kawasan Sehat NTB and the achievement of the program indicators. Conclusions: Kawasan Sehat program for stunting intervention has been successful according to input, process, and output. Community empowerment should continuously be strengthened to encourage communities to adopt clean and healthy living behaviors.